Customer perceived benefits and customer citizenship behaviour in Pakistan airline industry : Mediating role of relationship quality and moderating role of conspicuous consumption - Hassan, Shahzad (2024)
Research on customer citizenship behavior has received less attention in the airline industry, and studies investigating the importance of customer citizenship behavior are lacking. This study investigates the influence of (i) relationship quality on customer citizenship behavior, and (ii) customer perceived benefits on relationship quality in the Pakistani airline industry. Furthermore, the mediating role of relationship quality and the moderating role of conspicuous consumption in this relationship are also examined. Data collected from 360 passengers of Pakistani airlines through systematic sampling were analyzed using partial least squares structural equation modeling (PLS-SEM) via SmartPLS 3.3. The results reveal that customer citizenship behavior in the Pakistani airline industry is determined by relationship quality and customer-perceived benefits, such as functional benefits and relational benefits. Moreover, relationship quality partially mediates the relationship between functional benefits and customer citizenship behavior while it fully mediates the relationship between relational benefits and customer citizenship behavior. Additionally, conspicuous consumption moderates the relationship between relationship quality and customer citizenship behavior. This study makes a valuable contribution to the existing knowledge by utilizing social exchange theory as the underlying framework and incorporating the theory of conspicuous consumption as a supporting theory to examine the direct impact of customer-perceived benefits, the mediating role of relationship quality, and the moderating role of conspicuous consumption in the Pakistan airline industry within a single framework. Managers and decision-makers in the airline industry should prioritize the enhancement of customer-perceived benefits by providing functional benefits and relational benefits to create a positive customer experience, foster customer loyalty, and nurture long-lasting relationships with customers. By understanding these dynamics, managers can make informed decisions to enhance customer satisfaction and loyalty, ultimately leading to business growth and success